Monitoring Pertumbuhan dan Produktivitas Tanaman Aren (Arenga pinnata Merr) di Hutan Kemasyarakatan Aik Bual Kabupaten Lombok Tengah: Growth and Productivity Monitoring of Sugar Palm (Arenga pinnata Merr) in the Aik Bual Community Forest, Central Lombok Regency - Sani, Ahmad Luqman; Nurul Chaerani; Aji, Irwan Mahakam Lesmono (Jurnal Silva Tropika, 2025)
ABSTRACT The sugar palm (Arenga pinnata Merr) is a multipurpose tree species of considerable ecological and economic significance, naturally occurring in forest ecosystems, including the Community Forest (HKm) of Aik Bual, Central Lombok. This study aimed to assess population dynamics and productivity changes of sugar palm over a five-year period (2019–2024). A complete enumeration was conducted, recording all individuals and classifying them by growth stage (seedling, sapling, pole, and tree) and productivity category (non-productive, nearly productive, productive, and no longer productive). Results showed that the population increased from 433 individuals in 2019 to 1,195 individuals in 2024, representing an increase of 762 individuals (approximately 176%). In 2024, the population consisted of 287 seedlings, 339 saplings, 230 poles, and 88 trees classified as non-productive; 1 pole and 122 trees as nearly productive; 88 trees as productive; and 40 trees as no longer productive. This population growth was supported by favorable environmental conditions, including fertile Mollic Andosol soils, annual rainfall of 1,629–2,823 mm/year, and mean temperatures of 26–27°C.   Keywords: aik bual community forest, growth, monitoring, productivity, sugar palm   ABSTRAK Aren (Arenga pinnata Merr) merupakan jenis tanaman serbaguna (Multi Purpose Tree Species) yang memiliki nilai ekologis dan ekonomis tinggi, yang tumbuh secara alami di Kawasan hutan, termasuk di Hutan Kemasyarakatan (HKm) Aik Bual, Lombok Tengah. Penelitian ini bertujuan untuk mengetahui perkembangan tanaman aren di HKm Aik Bual dari sisi pertumbuhan dan produktivitas dalam kurun waktu lima tahun yaitu tahun 2019-2024. Metode yang digunakan adalah sensus (sampling jenuh) terhadap seluruh individu tanaman aren, dengan paremeter yang diamati meliputi tingkat pertumbuhan (Semai, Pancang, Tiang, dan Pohon) dan tingkat produktivitas (Belum Produktif, Hampir Produktif, Produktif, dan Sudah Tidak Produktif). Hasil menunjukkan peningkatan populasi tanaman aren dari 433 individu pada tahun 2019 menjadi 1.195 individu pada tahun 2024, bertambah sebanyak 762 individu atau naik sekitar 176%. Komposisi aren pada tahun 2024 meliputi 287 individu tingkat semai, 339 individu tingkat pancang, 230 individu tingkat tiang, dan 88 individu tingkat pohon yang semuanya masuk dalam kategori belum produktif. Pada kategori hampir produktif terdapat satu individu tiang dan 122 individu pohon, sementara itu, 88 individu pohon telah memasuki kategori sudah produktif, dan 40 individu pohon lainnya tergolong sudah tidak produktif. Peningkatan populasi aren didukung oleh kondisi lingkungan seperti jenis tanah yang sesuai, seperti jenis tanah Andosol Molik yang subur, curah hujan tahunan antara 1.629–2.823 mm/tahun, dan suhu rata-rata antara 26–27°C   Kata kunci: aren, HKm aik bual, monitoring, pertumbuhan, produktivitas